Purification of a new isoform of laccase from a Marasmius quercophilus strain isolated from a cork oak litter (Quercus suber L.) - Farnet, A. M.; Criquet, S.; Pocachard, E.; Gil, G.; Ferré, E. (MYCOLOGIA, 2002)
A new isoform of laccase from Marasmius quercophilus is described in this study. The strain of this white-rot fungus was isolated for the first time on a cork oak litter. This isoform exhibited certain common properties of laccases (a molecular weight of 65 Kda, an optimum pH of 6.2 with syringaldazine). But this laccase has also particularly novel features: the best activity measured was observed at high temperatures (80 C) and this isoform was not inhibited with EDTA. Furthermore, this induced laccase was able to transform most of the aromatic compounds tested without the addition of mediators to the reaction mixture, and the transformation of certain chlorophenols (2-chlorophenol and 2,4-dichlorophenol) by a laccase isoform from M. quercophilus is reported here for the first time. We also demonstrate the importance of 2,2'-azinobis(3-ethylbenzthiazoline-6-sulfonate) (ABTS) as a mediator since it allowed veratryl alcohol and p-hydroxybenzoic acid transformation. Moreover, new products of transformation were observed using the combination of ABTS with this isoform of laccase.
The following values have no corresponding Zotero field: pub-location: PUBLICATIONS DEPT, BRONX, NY 10458 USA publisher: NEW YORK BOTANICAL GARDEN
Keywords: aromatic compounds; mediator; polyphenoloxidase; white-rot fungus

Biochemical and molecular characterization of a laccase from Marasmius quercophilus - Dedeyan, B.; Klonowska, A.; Tagger, S.; Tron, T.; Iacazio, G.; Gil, G.; Le petit, J. (APPLIED AND ENVIRONMENTAL MICROBIOLOGY, 2000)
The basidiomycete Marasmius quercophilus is commonly found during autumn on the decaying litter of the evergreen oak (Quercus ilex L.), a plant characteristic of Mediterranean forest. This white-rot fungus colonizes the leaf surface with rhizomorphs, causing a total bleaching of the leaf. In synthetic liquid media, this white-rot fungus has strong laccase activity. From a three-step chromatographic procedure, we purified a major isoform to homogeneity, The gene encodes a monomeric glycoprotein of approximately 63 kDa, with a 3.6 isoelectric point, that contains 12% carbohydrate, Spectroscopic analysis of the purified enzyme (UV/visible and electron paramagnetic resonance, atomic absorption) confirmed that it belongs to the ``blue copper oxidase{''} family. With syringaldazine as the substrate, the enzyme's pH optimum was 4.5, the optimal temperature was 75 degrees C, and the K-m was 7.1 mu M. The structural gene, lac1, was cloned and sequenced. This gene encodes a 517-amino-acid protein 99% identical to a laccase produced by PM1, an unidentified basidiomycete previously isolated from wastewater from a paper factory in Spain. This similarity may be explained by the ecological distribution of the evergreen oak in Mediterranean forest.
Keys: APSKeys: APSThe following values have no corresponding Zotero field: pub-location: 1325 MASSACHUSETTS AVENUE, NW, WASHINGTON, DC 20005-4171 USA publisher: AMER SOC MICROBIOLOGY
Keywords: Basidiomycete; litter; Marasmius quercophilus; mediterranean forest; Quercus ilex L.; structural genes